MANAGEMENT OF EARLY CHILDHOOD CHARACTER EDUCATION AT PAUDQU INSTITUTION - Puji Astuti; R. Madhakomala (Ravine Publisher, 2024)
Character education has a very important role in changing a person's behaviour. Character education begins to be formed from an early age because early childhood is the period with the most potential for habituation in the process of character formation in children. Forming good character from an early age will influence a child's character when they grow up. Character education is not only limited to theory but is carried out by providing good examples to young children. To be able to carry out effective and efficient character education, good character education management is needed. Character Management explains management in instilling values that must be applied in everyday life. The aim of this research is to find a clear description and analysis of Character Education Management starting from planning, implementation and evaluation at the Al-Qur'an Early Childhood Education Institution (PaudQu) so that character education can be implemented well and the aim of character education is every lesson can be achieved well. This type of research is a literature review. The data used in preparing this article came from various literature related to the problems studied.